Implementation of PPKN Learning for Students at SMP Negeri 1 Lingsar - Ida Ayu Suci Padmawati; Dila Aprillia; Mohamad Mustari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
In Pancasila and Civics Education, implementation is essential so that during civics learning, students can develop awareness and understanding of civic values, develop attitudes and behaviors that reflect a love for the homeland and the nation's cultural heritage, and strengthen understanding of the Indonesian archipelago's character and the importance of national resilience among the younger generation currently pursuing and developing themselves in science, technology, and the arts. The research used a case study with qualitative research methods, and data collection utilized observation, interviews, and documentation. Challenges faced by educators at Lingsar 1 Public Middle School included students in each class who were still lazy during Pancasila and Civics Education and a lack of student enthusiasm during the presentation and Q&A sessions. Therefore, efforts are being made to implement Pancasila and Civics Education by instilling a sense of nationalism in children through the application and study of the principles of Pancasila. The effectiveness of Pancasila and Civics Education in schools is being assessed to foster student awareness.